Collaboration between forensic odontology and forensic pathology is crucial in Disaster Victim Identification - Muhammad Salman Khan; Antonius Winoto Suhartono; Elza Ibrahim Auerkari (Eduvest - Journal of Universal Studies, 2024)
While forensic pathologists have always played a pivotal role in victim identification after mass casualties, new developments in forensic methods have given forensic anthropologists more agency in positively identifying individuals who were previously unidentifiable.This review aims to contribute to the refinement of diagnostic tools, ensure optimal utilization of remnants and information available, and emphasize the contributions of forensic pathologists and forensic odontologist to victim identification and the importance of forensic pathologists and forensic odontologist in the criminal justice system. Considering the Interpol DVI Guide's emphasis on fingerprints, dental examinations, and DNA as primary identifiers, the forensic pathologist's role as the leader of a multidisciplinary team of experts in a disaster situation has taken on new significance. This is due to the forensic pathologist's and forensic odontologist training and experience leading similar teams during routine operations at a forensics institute. This thorough examination highlights the utmost significance of the job carried out by forensic pathologists and forensic odontologist. They play an important role in the judicial process by providing expert views in criminal investigations. Their expertise ensures accurate identification of victims and provides critical evidence that is necessary for holding offenders responsible. Their contributions are fundamental to the administration of justice, highlighting the great importance of their function in the overall structure of the criminal judicial system.